Pengaruh Lembar Kerja Siswa Menggunakan Software Prezi Terhadap Minat Belajar Siswa Mata Pelajaran PPKn Kelas VIII Smpn 30 Muaro Jambi - Musdalifah, Musdalifah; Irwan, Irwan; Simaremare, Tohap Pandapotan (Citizenship Education, Faculty of Education, Jambi University, 2022)
This research was conducted with the aim of knowing the effect of student worksheets using Prezi software on interest in learning class VIII in chapter VI, this research was conducted at SMPN 30 Muaro Jambi in the even semester of the 2021/2022 academic year. The results of the calculation of the increase in the NGain score show that the average Ngain score for the experimental class is 6.3980 which is included in the High category while the average Ngain score for the control class is -2.3717 which is included in the Low category. with the reported data normally distributed and uniform. Then based on the